Drawing them in: professional perspectives on the complexities of engaging 'culturally diverse' young people with sexual and reproductive health promotion and care in Sydney, Australia. Issue 4 (3rd April 2017) - Botfield, Jessica R.; Newman, Christy E.; Zwi, Anthony B.
Abstract: Young people from minority ethnic, migrant and refugee backgrounds are widely recognised as being under-served by mainstream sexual and reproductive healthcare in developed economy nations. This paper documents the views of professionals in Australia on the complexities of, and best practice approaches to, engaging members of this group with sexual and reproductive health promotion and care. Semi-structured interviews were conducted with 23 purposively selected key informants (health service providers, policymakers, academics and community advocates). Interviews were transcribed verbatim and coded in NVivo10 using interpretive thematic analysis. Principles of 'cultural competence' were employed to structure the interpretation of findings. Five key themes reveal pivotal aspects of how professionals work in, and make sense of, this complex field. These may be summarised as: (1) appreciating the complexities of cultural diversity; (2) recognising structural barriers and disincentives to engagement; (3) normalising sexual health; (4) balancing 'youth-friendly' and 'culturally-competent' priorities; and (5) going beyond simple translation. As migration to Australia continues to diversify the population, an integrated, national approach to the design and delivery of sexual and reproductive health promotion and care would be of value, along with training and support for those involved. Implications may have resonance for other countries similarly engaged in facilitating the successful settlement of migrants and refugees.